THE PROSPECT OF IMPROVING RICE CROPPING INDEX 400 IN WEST SUMATRA PROVINCE - Anggita Tresliyana; Erythrina Erythrina (Pusbindiklat - LIPI, 2012)
Rice Cropping Index 400 is an option to increase national rice production by 5% every year. The purpose of this study is to know the prospect of increasing cropping index of irrigated paddy to Rice Cropping Index 400 in West Sumatra Province in terms of agro ecosystem sustainability and financial feasibility. The assessments used primary and secondary data. Quantitative analysis was applied to analyze total revenue and revenue to cost ratio (R/C). The results indicated that Rice Cropping Index 400 is feasible in West Sumatra Province in terms of agro ecosystem sustainability and financial feasibility with R/C value 2,22. The scenario of Rice Cropping Index 400 is to plant rice varieties Silugonggo and Ciherang, with “culikan” seedbed 15 days before harvest.